2023
DOI: 10.1002/ange.202216720
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Near‐unity Photoluminescence Quantum Yields in Organic‐Inorganic Hybrid Antimony (III) Chlorides with the [SbCl5] Geometry

Abstract: Hybrid organic-inorganic antimony halides have attracted increasing attention due to the non-toxicity, stability, and high photoluminescence quantum yield (PLQY). To shed light on the structural factors that contribute to the high PLQY, five pairs of antimony halides with general formula A 2 SbCl 5 and A 2 Sb 2 Cl 8 are synthesized via two distinct methods and characterized. The A 2 SbCl 5 type adopts square pyramidal [SbCl 5 ] geometry with near-unity PLQY, while the A 2 Sb 2 Cl 8 adopts seesaw dimmer [Sb 2 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…A comparison is made between the band gap, the optical properties and Sb-Sb distance of these two halides and those of some antimony-based halides of the same structure that have been reported (Table 1). 29 The result shows that (NYP) 2 Sb 2 Cl 8 has a prolonged decay time and a smaller band gap than other A 2 Sb 2 Cl 8 halides. In addition, the luminescence properties of (NYP) 2 SbCl 5 and other five-coordinated Sb-based halides have been compared (Table S5 †).…”
Section: Resultsmentioning
confidence: 90%
“…A comparison is made between the band gap, the optical properties and Sb-Sb distance of these two halides and those of some antimony-based halides of the same structure that have been reported (Table 1). 29 The result shows that (NYP) 2 Sb 2 Cl 8 has a prolonged decay time and a smaller band gap than other A 2 Sb 2 Cl 8 halides. In addition, the luminescence properties of (NYP) 2 SbCl 5 and other five-coordinated Sb-based halides have been compared (Table S5 †).…”
Section: Resultsmentioning
confidence: 90%
“…Recent studies have shown that a longer Sb─Sb distance is beneficial for more expressed lone pairs of Sb 3+ to produce a confined STE, thus yielding highly efficient emission. [20] For close Sb─Sb distance in even distorted lattice imply a high concentration of emission centers in Sb 3+ -doped (TBP)SnCl 5 •DMF, the more electronphonon coupling and larger concentration quenching lead to stronger non-radiation processes. In our system, the PLQY of Sb 3+ -doped (TBP) 2 SnCl 6 is significantly higher than Sb 3+ -doped (TBP)SnCl 5 •DMF, which supports the fact that the former has an ideal Sb─Sb distance for emission.…”
Section: Resultsmentioning
confidence: 99%